Pengaruh Metode ABA Terhadap Kemampuan Memahami Instruksi Sederhana Pada Siswa Autis Kelas 2 Di SLB C TPA Jember - Akbar, Nurul Fadilah; Udhiyanasari, Khusna Yulinda; Nurhidayati, Arifah (Educatio, 2026)
Autism itself is a complex developmental disorder caused by abnormal brain function that impacts communication, social interaction, behavior, sensory development, and learning abilities. Most autistic students still experience difficulties responding to simple instructions during the learning process. The formulation of the problem in this study is whether there is an effect of the ABA (Applied Behavior Analysis) method on the ability to understand simple instructions in grade 2 autistic students at SLB C TPA Jember. The purpose of this study is to determine the effect of the ABA (Applied Behavior Analysis) method on the ability to understand simple instructions in grade 2 autistic students at SLB C TPA Jember. The method used in this study is Single Subject Research (SSR) with an A-B design. Data analysis in this study uses data from the baseline phase (A) and the intervention phase (B). The baseline phase (A) is the observation phase on the subject by observing the ability to understand simple instructions, and the intervention phase (B) is the observation after the subject has been given or given intervention. In this study, there are two variables that are the objects of study, namely the independent variable and the dependent variable. The independent variable is the variable that influences the dependent variable, while the dependent variable is the target behavior ability. The independent variable in this study is the Applied Behavior Analysis (ABA) method. The dependent variable, or target, is the ability to understand simple instructions in autistic students.